Assessing the effects of internal (trophic structure) and external (fishing and environment) forcing factors on fisheries off central Chile : basis for an ecosystem approach to management - Alarcón, Sergio Eduardo Neira (Department of Biological Sciences, 2014)
Includes abstract.